Equilibrium Search Unemployment with Explicit Spatial Frictions - Etienne Wasmer; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2004)
Assuming that job search efficiency decreases with distance to jobs, workers' location in a city depends on spatial elements such as commuting costs and land prices and on labour elements such as wages and the matching technology. In the absence of moving costs, we show that there exists a unique equilibrium in which employed and unemployed workers are perfectly segregated but move at each employment transition. We investigate the interactions between the land and the labour market equilibrium and show under which condition they are interdependent. When relocation costs become positive, a new zone appears in which both the employed and the unemployed co-exist and are not mobile. We demonstrate that the size of this area goes continuously to zero when moving costs vanish. Finally, we endogeneize search effort, show that it negatively depends on distance to jobs and that long and short-term unemployed workers coexist and locate in different areas of the city.
Keywords: E24; J41; R14; 330; Local Labour Markets; Relocation Costs; Search Effort; Job Matching; Friktionelle Arbeitslosigkeit; Arbeitsmobilität; Arbeitsplatzsuchmodell; Arbeitsmarkttheorie